NILAI-NILAI PRIBADI - Agus Hasan Pura A (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
Values are changes. Values guide people on behave, so it must be good values. Family’s values and religion’s values are diminishing, personal values are the substitute. This is the problem for marketers but more dangerous for the nation in the future. So, government, family, religion and education institutes have to find out the solutions.